2009
DOI: 10.1093/brain/awp271
|View full text |Cite
|
Sign up to set email alerts
|

Voxel-based morphometry reveals reduced grey matter volume in the temporal cortex of developmental prosopagnosics

Abstract: Individuals with developmental prosopagnosia exhibit severe and lasting difficulties in recognizing faces despite the absence of apparent brain abnormalities. We used voxel-based morphometry to investigate whether developmental prosopagnosics show subtle neuroanatomical differences from controls. An analysis based on segmentation of T1-weighted images from 17 developmental prosopagnosics and 18 matched controls revealed that they had reduced grey matter volume in the right anterior inferior temporal lobe and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
173
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(184 citation statements)
references
References 82 publications
(161 reference statements)
10
173
1
Order By: Relevance
“…showed a selective marked reduction of ILF in the right hemisphere, whereas IFOF showed only a mild asymmetry, might explain the prominent cognitive disorder, i.e., modality-specific prosopagnosia, shown by our patient. Indeed, a reduction in the microstructural integrity of both ILF and IFOF bilaterally has been reported in congenital prosopagnosic subjects by Thomas et al (2009).I n DP, developmental hypotrophy of bilateral ILF and IFOF (Thomas et al, 2009) and of the anterior part of fusiform gyri (Behrmann et al, 2007;Garrido et al, 2009) would impair maturation of normal face processing skills, and preclude formation of any efficient compensatory pathway. In the present patient PP was related to the atrophy of the rILF, related to progressive neuronal loss, affecting both grey and white matter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…showed a selective marked reduction of ILF in the right hemisphere, whereas IFOF showed only a mild asymmetry, might explain the prominent cognitive disorder, i.e., modality-specific prosopagnosia, shown by our patient. Indeed, a reduction in the microstructural integrity of both ILF and IFOF bilaterally has been reported in congenital prosopagnosic subjects by Thomas et al (2009).I n DP, developmental hypotrophy of bilateral ILF and IFOF (Thomas et al, 2009) and of the anterior part of fusiform gyri (Behrmann et al, 2007;Garrido et al, 2009) would impair maturation of normal face processing skills, and preclude formation of any efficient compensatory pathway. In the present patient PP was related to the atrophy of the rILF, related to progressive neuronal loss, affecting both grey and white matter.…”
Section: Discussionmentioning
confidence: 99%
“…Within these regions, that are part of the so-called 'core system' for face processing (Haxby et al, 2000), the fusiform gyrus seems to be especially important for processing facial identity. More recently, an important role in face recognition has also been ascribed to the anterior inferior temporal lobe (Allison et al, 1994b(Allison et al, , 1999Rajimehr et al, 2009;Tsao et al, 2008), particularly in individuals with developmental prosopagnosia (DP), who may show reduced volume of the anterior part of fusiform gyri (Behrmann et al, 2007;Garrido et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…If there are any perceptual or working memory impairments in DP, these may be specific to representations of facial identity, and leave the representation of emotional expression unaffected. This has been suggested by studies showing that DPs are relatively normal in their ability to recognise categorically distinct basic emotions (Duchaine, Parker, & Nakayama, 2003;Humphreys, Avidan, & Behrmann, 2007;Palermo et al, 2011), more subtle and complex expressions (Duchaine et al, 2003;Duchaine, et al, 2007;Palermo et al, 2011) and are also able to successfully complete expression matching tasks (Bentin, DeGutis, D'Esposito, & Robertson, 2007;Garrido et al, 2009;Lee et al, 2010). DPs also show typical neural responses to emotional versus neutral faces (Avidan et al, 2014;Dinkelacker et al, 2011, Furl et al, 2011Van den Stock et al, 2008;.…”
Section: Introductionmentioning
confidence: 91%
“…Neuroimaging studies of DP have shown that in contrast to face recognition disorders caused by brain injury (acquired prosopagnosia; Bodamer, 1947), the occipito-temporal "core" face processing network (e.g., Haxby, Hoffman, & Gobbini, 2000;Kanwisher, McDermott, & Chun, 1997) appears to be largely intact in DP (Avidan & Behrmann, 2009;Avidan, Hasson, Malach, & Behrmann, 2005;Avidan et al, 2014;Furl, Garrido, Dolan, Driver, & Duchaine, 2011;Hasson, Avidan, Deouell, Bentin, & Malach, 2003; but see also Berhmann, Avidan, Gao, & Block, 2007;Garrido et al, 2009). However, investigations of face-specific event-related potential (ERPs) in DP are now beginning to reveal systematic differences between DPs and control participants, both at early visual-perceptual stages of face processing, and at later memory-related stages associated with the recognition of facial identity (see Towler, Fisher, & Eimer, in press, for review).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, if actual differences in processing strategy or biological markers of DP and super-recognition are observed, this would be stronger evidence that the two terms refer to qualitatively different groups of people. There is some evidence to support this in individuals with DP, given recent neurological findings that suggest structural atypicalities within critical regions implicated in face-processing (e.g., Behrmann, Avidan, Gao, & Black, 2007;Burns, Tree, & Weidemann, 2014;Garrido et al, 2009;Song et al, 2015).…”
Section: Developmental Prosopagnosia: Historical Backgroundmentioning
confidence: 98%